Grammatical Change in the Verb Phrase in Contemporary Philippine English - Collins, Peter (Asiatic: IIUM Journal of English Language and Literature, 2016)
This paper presents the findings of a diachronic corpus-based study of selected categories of the verb phrase – the progressive aspect, the passive voice, the present perfect aspect, the modals and quasi-modals – in contemporary Philippine English and its colonial parent variety, American English. Frequencies were determined for the verb phrase categories in the Philippine and American components of the early 2010s Corpus of Global Web-based English. These are compared with the findings of earlier studies by Collins and associates of Philippine English, and by Leech and associates of American English, in the 1960s and 1990s. The trajectories of the grammatical variables over the half-century from the early 1960s to the early 2010s are traced, and the implications of the findings for the contentious issue of the evolutionary status of PhilE are explored.